2022
DOI: 10.4103/sja.sja_236_22
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Pain Management in Bariatric Anesthesia

Abstract: Weight loss (bariatric) surgery is the most commonly performed elective surgical procedure in patients with morbid obesity. In this review, we provide an evidence-based update on perioperative pain management in bariatric anesthesia. We mention some newer preoperative aspects—medical optimization, physical preparation, patient education, and psychosocial factors—that can all improve pain management. In the intraoperative period, with bariatric surgery being almost universally performed laparoscopically, we emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
5
0
3
Order By: Relevance
“…Opioids should be used sparingly to avoid opioid-dependency and respiratory depression. 18 Instead, recent systematic review conducted by De Cassai et al suggested the use of transabdominal plane (TAP) block due to its efficacy in reducing PONV following BMS. 19 Patients undergoing BMS have been reported to be at a higher risk of developing VTE after surgery due to their hypercoagulability state and other existing comorbidities.…”
Section: Postoperative Phasementioning
confidence: 99%
“…Opioids should be used sparingly to avoid opioid-dependency and respiratory depression. 18 Instead, recent systematic review conducted by De Cassai et al suggested the use of transabdominal plane (TAP) block due to its efficacy in reducing PONV following BMS. 19 Patients undergoing BMS have been reported to be at a higher risk of developing VTE after surgery due to their hypercoagulability state and other existing comorbidities.…”
Section: Postoperative Phasementioning
confidence: 99%
“…(32,34) Entre los anestésicos utilizados para la cirugía laparoscópica se encuentra el Propofol, que se utiliza para el mantenimiento anestésico a través de administración total vía intravenosa (TIVA), debido a que el sevoflurano provoca mayor incidencia de náuseas y vómitos postoperatorios. (5) El tratamiento con analgesia debe ser administrado antes que el paciente se despierte para evitar el dolor severo, facilitar su control y reducir los efectos adversos de la cirugía. Se inicia con terapias multimodales que combinan diferentes tipos de analgésico, estas deben adecuarse a la intensidad de dolor que el paciente refiera, son administradas por vía intravenosa.…”
Section: Vaccaro Y Col (25) 2022unclassified
“…Entre los opioides más utilizados en el dolor tenemos el tramadol, la morfina y el fentanilo. (5) La laparoscopia se realiza con técnicas de menor invasión logrando que los pacientes tengan: (2,35) • Un abordaje con incisiones reducidas. • Menor caída de la hemoglobina.…”
Section: Vaccaro Y Col (25) 2022unclassified
See 1 more Smart Citation
“…Although the volume of estimated blood loss was higher in the NDB group, the ability of clinicians to correctly estimate blood loss is poor, [43][44][45][46] limiting the accuracy of these findings. Rather, we used objective metrics and variables, which were not amenable to clinician error.…”
Section: Strengths and Limitationsmentioning
confidence: 99%